Enhancement of the Stabilities and Intracellular Antioxidant Activities of Lavender Essential Oil by Metal-Organic Frameworks Based on β-Cyclodextrin and Potassium Cation - Ying Wang; Liang Wang; Jin Tan; Rong Li; Zi-Tao Jiang; Shu-Hua Tang (Polish Journal of Food and Nutrition Sciences)
Lavender ( Lavandula angustifolia ) is an important medicinal and aromatic plant. However, the application of lavender essential oil (LEO) is limited by its instability, low solubility and high volatility. Therefore, to improve the stabilities and antioxidant activities of LEO and thereby expand the applications, LEO was microencapsulated by metal-organic frameworks based on β-cyclodextrin and potassium cation (K-βCD-MOFs) with different mass core/wall ratios. The results showed that the best inclusion rate was 96.67% with the ratio of 1:10. Then, the optimum inclusion product was characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM). The thermal and pH stabilities and the intracellular antioxidant activities were also studied. The results showed that the stabilities of the oil with K-βCD-MOFs inclusions and their abilities to resist acid and alkali were significantly stronger than those of LEO itself. In addition, the intracellular antioxidant activities of LEO were also enhanced by the K-βCD-MOFs inclusion. These results suggested the potential of K-βCD-MOFs as carriers for essential oils in food industry applications.